Xbox Kinect Sports Vs. Nintendo Switch Sports and Their Effects on Body Composition and Physical Performance in Older Females: A Randomized Controlled Trial - Herrera-Valenzuela, T; Cid-Calfucura, I (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Background/Objectives: This study aimed to compare the effects of Xbox Kinect Sports (XKS) regarding Nintendo Switch Sports (NSS) and an inactive control group (CG) on body composition (body fat percentage, BFP; and fat-free mass) and physical performance (maximal isometric handgrip strength, MIHS; 30-s chair stand, 30-S; timed up-and-go, TUG; sit-and-reach; and 2-min step) in physically inactive older females. Methods: A randomized controlled trial study was conducted with three parallel groups: XKS (n = 13), NSS (n = 14), and CG (n = 16) considering three weekly 60-min sessions for 12 weeks with pre- and post-assessments. Results: A two-factor mixed analysis of variance (ANOVA) model with repeated measures was performed to measure the time × group effect. Multiple comparisons revealed significant differences in BFP (F(2,18) = 6.12; p = 0.005; ηp2 = 0.226, large effect), 30-S (F(2,18) = 20.7; p = 0.000; ηp2 = 0.496, large effect), TUG (F(2,18) = 10.0; p = 0.000; ηp2 = 0.323, large effect), sit-and-reach (F(2,18) = 37.3; p = 0.000; ηp2 = 0.640, large effect), and 2-min step (F(2,18) = 9.85; p = 0.000; ηp2 = 0.319, large effect) in favor of XKS regarding NSS and CG. The intragroup results only present in XKS a significant decrease in BFP (p = 0.02; d = 0.98) and significant improvements in the 30-S (p = 0.000; d = 1.88), TUG (p < 0.01; d = 2.00), sit-and-reach (p = 0.003; d = 2.58), and 2-min step (p = 0.004; d = 1.05). Conclusions: training using XKS significantly decreases BFP and improves 30-S, TUG, sit-and-reach, and 2-min step in physically inactive older females. © 2024 by the authors.